10. Evaluating Vendor Supplied Information - Fahy, Patrick J. (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2002)
Distance educators are not normally equipped by their training or experience for the complex task of evaluating technologies. One of the areas of potential disadvantage is in interpreting information provided by vendors themselves, and in relating effectively with sales, marketing and technical representatives. An objective and thorough product evaluation requires that information be selected, and sometimes generated, to aid the process. Vendors may agree to provide additional information, including direct experience with their products, if evaluators know what to ask for and what to expect from vendors.